Effect of Paclobutrazol Application Field on Seed Rhizome Quality of Ginger during Storability - Devi Rusmin (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
Maintaining the availability of high quality of seed on-time is one of the major problems in the production of large white ginger seed rhizomes (LWG). LWG seeds cannot be stored for a long period of time because it is easily wrinkled and sprouted during the storage. This study aimed to understand the effect of PBZ treatment time and concentration on the quality of LWG seeds during the storage. This study used a randomized square experimental design with three replications. The main plot is the time of application of paclobutrazol: 1) 4 months after planting (MAP) and 2) 5 MAP, and as subplots are five levels of PBZ concentration : 0, 100, 200, 300 and 4 00 ppm. The results showed the treatment of PBZ 400 ppm at 4 and 5 MAP was the best concentration in increasing the shelf life of LWG seeds: growth speed (4.8% / etmal ), seedling height (60.38 cm) and dry weight of seedlings (1.51 g) after stored for 4 months compared with no PBZ treatment.